Control-Lab-in-a-Box: Bridging the Gap between Control Theory and Engineering Practice (UK and Ireland Engineering Education Research Network Conference Proceedings 2023, 2024)
Traditional control engineering teaching methods heavily rely on abstract mathematical concepts, often leaving students puzzled about real-world applications. Common simulation tools, such as MATLAB and Simulink provide a good visual demonstration but don't necessarily bridge the gap between theory and application. The proposed ‘lab-in-a-box’ approach offers a tangible method for students to connect control theory with a practical control engineering experience. The literature has observed a shift towards such portable labs, given the advancements in compact computing devices such as Raspberry Pi and Arduino boards in electronics and control teaching. The primary goal of these labs is to deliver an authentic engineering experience with essential hardware. Evaluation of this method, through the student module evaluation questionnaire (MEQ), revealed a significant increase in student satisfaction after its introduction. While the results are promising, challenges remain, such as the initial set-up of the kits. However, the ‘lab-in-a-box’ is found to be a valuable tool in control engineering education, bridging the gap between theoretical and practical understanding. An on-going development includes updating of the kits to match future engineering challenges and needs, e.g., electrification and autonomy of vehicles.